Evaluation of the Mast ID and API 50CH systems for identification of Listeria spp. - Kerr, K G (1990)
A multipoint inoculation technique (Mast ID) for the identification and species determination of Listeria monocytogenes (sensu strictu) and six other species of the genus Listeria was evaluated. This was compared with the commercially available API 50CH system. Both methods successfully identified all 123 strains tested. The Mast ID system is inexpensive and utilizing a multipoint inoculation technique permits the screening of up to 21 isolates per 9-cm petri dish. The API 50CH system was more expensive and time consuming and is therefore suitable only for the examination of smaller numbers of strains.